Bank systemic risk and corporate investment: Evidence from the US - Adachi-Sato, Meg; Vithessonthi, Chaiporn * (Elsevier, 2017)
In this paper, we use three measures that arguably capture two dimensions of “bank systemic risk”, namely, (1) bank funding maturity and (2) bank asset commonality, to empirically test whether bank systemic risk has a positive effect on corporate investment. We document that in a sample of publicly listed firms in the United States over the period 1991-2013, bank systemic risk is positively associated with the firm-level investment ratio after controlling for a large set of country-level and firm-level variables. In addition, we show that a firm’s leverage strengthens the positive effect of bank systemic risk on corporate investment, suggesting that more financially constrained firms experience a larger effect of bank systemic risk on corporate investment than less financially constrained firms.